THE SENSORIMOTOR CONTROL OF HUMAN STANDING POSTURE: AN INVESTIGATION INTO THE RELATIONSHIP AMONG ATTENTION, VISUAL FEEDBACK AND AGE - YEH, TING TING (My University, 2014)
Maintaining upright posture is seemingly an automatic task in younger adults, but it may require additional resources in late adulthood due to decreases in sensorimotor and cognitive functions. The thesis used a dual-task paradigm to investigate age-related changes in relation to the secondary task and context-dependent factors attributes to postural control. The postural task involved visuomotor tracking. Successfully performing the visuomotor task necessitated proper sensory feedback, motor response, and sensorimotor integration. Moreover, we used silent counting as a cognitive task to investigate attentional demands on postural control and age-related difference in cognitive processing.
We first investigated the relative contributions of visual feedback delay and cognitive task load on postural dynamics as well as age-related difference in this effect. Our results supported distinct timescale mechanisms for postural control. Moment-to-moment center of pressure fluctuations are dependent on cognitive performance during delayed visual feedback postural control. Also, we demonstrated the increased role of vision with age in postural control. Next, we investigated whether postural control improved when performing a cognitive task with an internal focus of attention. We found that devoting less attention internally by performing a cognitive dual-task enhanced postural control in young adults. Yet, the age-related declines diminish the attentional allocation ability. Lastly, we investigated how older and younger adults differ in employing sensorimotor strategies in a dual-task situation. Our results suggested that age-related changes in postural control may degrade the flexible coordination of the sensory feedback and motor execution. Furthermore, diminished cognitive and attentional capacities may alter postural performance in dual-task conditions.
This thesis adds to the current understanding of the role of sensorimotor processing, attentional influence and age in the control of posture. Our data provide convergent evidence that deterioration of peripheral sensorimotor systems and reduced flexibility in central information processing are responsible for the age-related differences in postural control.
Keywords: Aging; Postural control; Attention; Visual feedback; Cognitive dual task; Motor Control; Motor Control